Stability in Functional Integro-differential Equations of Second Order with Variable Delay - Cemil Tunc; Melek Gozen (Institute for Research and Community Services (LPPM) ITB, 2017)
In this paper, we investigate the stability of the zero solution of an integro-differential equation of the second order with variable delay. By means of the fixed point theory and an exponential weighted metric, we find sufficient conditions under which the zero solution of the equation considered is stable.